Cysteinyl leukotriene receptor antagonist epigenetically modulates cytokine expression and maturation of human myeloid dendritic cells. (August 2016) - Kuo, Chang-Hung; Yang, San-Nan; Kuo, Hsuan-Fu; Lee, Min-Sheng; Huang, Ming-Yii; Huang, Shau-Ku; Lin, Yi-Ching; Hsieh, Chong-Chao; Hung, Chih-Hsing
Abstract: Background: Cysteinyl leukotriene receptor antagonists are important controllers in treating asthma. Human myeloid DCs (mDCs) play critical roles in the pathogenesis of asthma. However, the effects of cysteinyl leukotriene receptor antagonist on human mDCs are unknown. Methods: To investigate the effects of cysteinyl leukotriene receptor antagonist on the function of human mDCs, circulating mDCs were isolated from six health subjects. Human mDCs were pretreated with montelukast and were stimulated with toll-like receptor (TLR) ligands lipopolysaccharide (LPS) or polyinosinic-polycytidylic acid (poly I:C). Tumor necrosis factor (TNF)-α and interleukin (IL)-10 were measured by ELISA. Intracellular signaling was investigated by pathway inhibitors, western blot and chromatin immunoprecipitation. Costimulatory molecules expression was investigated by flow cytometry. T cell polarization function of mDCs was investigated by measuring interferon (IFN)-γ, IL-13, IL-10 and IL-17A production by T cells using mDC/T cell coculture assay. Results: Montelukast suppressed TLR-mediated TNF-α expression via the NFκB-p65 and mitogen-activated protein kinase (MAPK)-JNK pathway, and enhanced TLR-mediated IL-10 expression via the MAPK-p38 pathway and epigenetic regulation by histone H3 acetylation. Montelukast suppressed LPS-induced CD80, CD86, CD40 and HLA-DR expression. Montelukast-treated mDCs suppressed IFN-γ and IL-13 production by T cells. Conclusion: Cysteinyl leukotriene receptor antagonist alters the function of human mDCs by epigenetically modulating cytokine expression, suppressing costimulatory molecules expression and inhibiting the ability to initiate Th1/Th2 responses. The effects of cysteinyl leukotriene receptor antagonist on human mDCs can be an important mechanism in treating asthma.